Kontrol Tegangan Self-Excited Induction Generator dengan Electronic Load Controller Terkontrol PID-GA - Ermanu Azizul Hakim; Rahayu Pandunengsih; Diding Suhardi; Novendra Setyawan (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Induction generator operation requires reactive power with external contactor. One of induction generator types, SEIG reactive power supplied by capacitor bank connected to generator terminal. SEIG is alternative energy conversion in small area or rural, SEIG has the main disadvantage of poor voltage regulation under various load conditions. ELC combine PID control which is optimized using Genetic Algorithm in order to maintain the stability of the voltage when the load varies. The result shows the SEIG system using ELC with PID-GA control worked to stable voltage in accordance with the standard with voltage tolerance of 10% when load change. The addition of GA to determine the value of the PID parameter where response system better with difference overshoot value start is 70.48%, when decrease load in 5 second by 44.3% and in the 10 second when increase load of 2 kW is 5.96% compared system with PID control without GA optimization.